Enlightenment and education: Baltasar de los Reyes Marrero and the Modern Philosophy program at the Universidad de Caracas, 1788 - Rojas, Reinaldo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The history of the Venezuelan colonial university is represented by the Real and Pontiicia Universidad de Caracas, created by Royal Charter on December 22nd1721. Hence, the reception of ideas coming from the Enlightenment era can be understood from the perspective of those educators who addressed the modernizationof their study programs and the reform of academic structures in in their professorship. The clergyman Baltasar de los Reyes Marrero (1752-1809), recognized as the founder of the Modern Philosophy program at the Real y Pontiicia Universidad de Caracas, is one of these outstanding educators. Thus, this paper focuses on the general biographical features, intellectual formation and pedagogical efforts carried out in the Venezuelan university by Baltasar de los Reyes.